Growth of The Kantong Semar (Nepenthes mirabilis (Lour.) Druce) On Various Plant Media - Astuti, Rina Budi; Suedy, Sri Widodo Agung; Nurchayati, Yulita; Setiari, Nintya (Metamorfosa: Journal of Biological Sciences, 2022)
Nepenthes mirabilis (Lour.) is a unique plant with a pitcher at the tip of the leaf. This species belongs to a rare category so needed to be preserved. One of the conservation efforts are the selection of the composition growing media for cultivation. This study aimed to found alternative planting media that can support the growth of Nepenthes other than sphagnum moss media. The research was conducted at the green house in Ngablak Village, Ngablak District, Magelang Regency from August to November 2020. This study used a Completely Randomised Design (CRD) with 4 treatments, sphagnum moss , roasted husk, roasted husk with cocopeat (3:1), sphagnum moss with cocopeat (3:1) given of 4 replications. Research parameter include, number of leaves, leaf length, leaf width, and plant height measured at 12 Weeks After Planting (WAP). Observation data were analysis by Analysist of Varians (ANOVA) and Duncan Multiple Range Test (DMRT) on a confidence level of 95%. The result showed that all treatment had a significant effect on the number of leaves, leaf length, leaf width, and plant height. The best planting medium was sphagnum moss with the time of appearance of the leaves (2,39 week), the highest number of leaves (11,25 sheet), and plant height (1,6 cm). the mixture media of roasted husk and cocopeat (3:1) produced growth that wsn’t different from sphagnum moss, so it was recommended to be a cheaper alternative media.   Keyword: Nepenthes mirabilis , sphagnum moss , roasted husks, cocopeat